COMPARATIVE LAW REPATRIATION INDONESIAN CITIZEN EX FOREIGN ISLAMIC STATE IRAQ AND SYIRIA ABOUT INDONESIA LAW AND ISLAMIC LAW - Badrul Munir; Yenny Sri Wahyuni; Teuku Awis Aulia (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2022)
The issue of citizen became the hot news on sosial meda country in Indonesian. On February 1 2020, the National Counter terrorism Agency exchanged international intelligence information with countries in the Middle East and got around 600 Indonesian citizens who were former combatants of the Islamic State of Iraq and Syria (ISIS). This polemic has become a hot topic of discussion among the government and the people of Indonesia about the fate of Indonesian citizens (WNI) whether they can be returned to their homeland or left alone in shelter camps in Syria. The formulation of the problem studied in this journal is to describe the views or opinion of Indonesian law on the concept of citizenship and explain the views of Indonesian law (law no. 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism) and Islamic law (Opinions of Imam Malik and Imam Syafii) concerning the repatriation of Indonesian citizens who were former combatants of the Islamic State of Iraq and Syria to Indonesia. In this study, the authors use normative research methods by conducting library research through the process of reading, researching, and reviewing ongoing discussions with this research. The results of this study indicate that in Indonesian law, referring to Law No. 5 of 2018, they must be repatriation to Indonnesia because they are the responsibility of the state in accordance with articles 43b, 43b, and 43d. whereas in Islamic law there is caution by asking them if they want to go back and repent for their actions, if they obey they can be repatriation to Indonesia, if not they are fought. and the decision will ultimately be left to the government about their fate.